ANTIBACTERIAL ACTIVITY IN DIFFERENT EXTRACTS OF LANTANA CAMARA AGAINST ENTEROPATHOGENS - Bhardwaj, Garima; Yadav, Shaili; Srivastava, Jyoti (Innovare Journal of Sciences, 2015)
Medicinal use of plants is the oldest form of healthcare known to mankind. India has a rich profusion of medicinal plants and 75% of its folk population is still using herbal preparations. Present study reports about antimicrobial potentiality of Lantana camara as its leaf extracts exhibit good antimicrobial, fungicidal, insecticidal and nematicidal properties and the plant might be a novel source of antimicrobial drug. Two enteropathogens as (A) - B. subtilis (positive, obligate aerobic) and (B) - E. coli (Gram-negative, facultative anaerobic) were used for the present study. Four solvent phases viz, methanol, ethanol, acetone and aqueous were used for extraction of antimicrobial agent. The screening of antimicrobial property was done by well diffusion method. Leaves of Lantana camara showed excellent antibacterial activity in all the solvent phases used against both E. coli as well as B. subtilis. Lantana is effective against both the bacteria.The aqueous extract showed minimum ineffective antimicrobial activity against E. coli and B. subtilis, where as acetone phase showed maximum activity against B. subtilis and ethanol against E. coli as shown in the terms of maximum zone of inhibition.